INFLUENCE OF DOSED BASED PROBIOTICS (Lactobacillus) ON BLOOD AND MICROBIAL INDICES OF BROILERS - Egbunike Chiazor Maryjan; Ironkwe Monica Ogochukwu; Boma Victor Iriso (Agricultura)
This study was carried to evaluate the effect of probiotics (Lactobacillus) on the blood parameters and microbial load of one hundred and twenty day old unsexed Abor Acres+ for a period of eight weeks. The birds were randomly allocated into four equally major groups (T1, T2, T3 and T4) each having two replicates with ten birds each. T1 is the control, while, the test ingredient was given at different levels of inclusion T2 (5ml), T3 (10ml) and T4 (15ml) at starter phase and T2 (15ml), T3 (20ml) and T4 (25ml) at the finisher phase respectively. On the 8th week of the experiment, blood and caecal samples droppings were collected and analyzed for blood and microbial load parameters. The results showed that haemoglobin was significantly higher in T2 (8.85±0.37) and lowest in T3 (8.22±0.47). White blood cell was highest in T3 (4.55±1.21) and significantly lowest (P<0.05) in T2 (1.00±0.89). High density lipoprotein was highest in T2 (1.80±0.37) and significantly lowest (P<0.05) in T1 (1.47±0.16) and T4 (1.47±0.13). Low density lipoprotein was highest in T4 (2.60±0.04) and significantly lowest (P<0.05) in T2 (2.03±0.26). Very low density lipoprotein was highest in T4 (0.82±0.02) and significantly lowest (P<0.05) in T2 (0.56±0.41). Total heterotrophic bacteria was highest in T4 (113.33±24.50) and significantly lowest (P<0.05) in T3 (75.33±11.38). Total coli form count was highest in T4 (77.59±25.91) and significantly lowest (P<0.05) in T2 (49.17±15.06). The utilization of probiotics had a beneficial effect on the gut health and blood indices of the broiler chicken.